2015
DOI: 10.1111/jopr.12315
|View full text |Cite
|
Sign up to set email alerts
|

Shear Bond Strength between Fiber‐Reinforced Composite and Veneering Resin Composites with Various Adhesive Resin Systems

Abstract: Within the limitations of this study, it was found that bonding of the veneering composite to bidirectional continuous fiber-reinforced substrate is influenced by the brand of the adhesive resin and veneering composite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Many studies were conducted to reach a consensus on the aging technique representing the closest to the relevant clinical scenario for composite-to-composite bonding (3,6,15) including thermocycling (16), water storage (17,18), citric acid immersion (11) and boiling (18). When a resin composite is subjected to the water storage, some damaging effects will occur on the resin composite surface including both hydrolysis and release of filler particles besides water absorption into the resin matrix (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies were conducted to reach a consensus on the aging technique representing the closest to the relevant clinical scenario for composite-to-composite bonding (3,6,15) including thermocycling (16), water storage (17,18), citric acid immersion (11) and boiling (18). When a resin composite is subjected to the water storage, some damaging effects will occur on the resin composite surface including both hydrolysis and release of filler particles besides water absorption into the resin matrix (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with the shear bond stress results. Weibull distribution has shown to be an alternative method for evaluation of the fracture probability of material (AlJehani et al , 2016).…”
Section: Discussionmentioning
confidence: 99%
“…FRCs have been proposed in many fields in dentistry for different purposes, namely, prosthodontics, endodontics, conservative dentistry, orthodontics, periodontology, and paediatric dentistry ( Table 1 ). Previous studies reported FRCs used for veneered fixed dental elements [ 15 ], root canal posts [ 16 ], filling resin composites [ 17 ], periodontal splints [ 18 ], orthodontic retainers [ 19 , 20 ], and orthodontic brackets [ 21 ]. In addition, temporary fixed dental prostheses (FDP) [ 22 ], reinforcement of removable devices, [ 23 ] and repairs of conventional restorations [ 24 ] have been reported.…”
Section: Introductionmentioning
confidence: 99%